2013
DOI: 10.1371/journal.pone.0058257
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Link Novel Loci to Endometriosis

Abstract: Endometriosis is a common gynecological condition with complex etiology defined by the presence of endometrial glands and stroma outside the womb. Endometriosis is a common cause of both cyclic and chronic pelvic pain, reduced fertility, and reduced quality-of-life. Diagnosis and treatment of endometriosis is, on average, delayed by 7–10 years from the onset of symptoms. Absence of a timely and non-invasive diagnostic tool is presently the greatest barrier to the identification and treatment of endometriosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
141
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(158 citation statements)
references
References 31 publications
9
141
2
5
Order By: Relevance
“…The risk alleles and their frequencies for all the nine SNPs in the Belgian replication cohort were comparable with the original studies ( Table 2; Albertsen et al, 2013;Nyholt et al, 2012;Painter et al, 2011;Sapkota et al, 2015b). Moreover, direction of effects for seven of the nine SNPs for either 'All' or 'Grade_B' endometriosis was also consistent with the published results.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The risk alleles and their frequencies for all the nine SNPs in the Belgian replication cohort were comparable with the original studies ( Table 2; Albertsen et al, 2013;Nyholt et al, 2012;Painter et al, 2011;Sapkota et al, 2015b). Moreover, direction of effects for seven of the nine SNPs for either 'All' or 'Grade_B' endometriosis was also consistent with the published results.…”
Section: Discussionsupporting
confidence: 87%
“…Our meta-analysis, including results from the current replication study and the published results, produced genome-wide significant evidence for six (rs7521902 near WNT4, rs13394619 in GREB1, rs6542095 in IL1A, rs7739264 near ID4, rs12700667 at 7p15.2, and rs1537377 near CDKN2B-AS1) of the nine implicated SNPs in either 'All' or 'Grade_B' endometriosis, after accounting for between-study heterogeneity using the RE2 model, wherever appropriate (Table 3). With the exception of rs1519761 at 2q23.3 reported by Albertsen et al (2013), the other two SNP loci (rs4141819 at 2p14 and rs10859871 near VEZT) also showed near genome-wide significance for 'Grade_B' endometriosis in the RE2 model (p = 3.63 × 10 −7 ) and for 'All' endometriosis in the fixed-effect model (p = 4.29 × 10 −7 ). The association signal for rs1519761 was the weakest ('All' , p = 5.62 × 10 −6 ; 'Grade_B' , p = 1.94 × 10 −6 ) among the nine risk loci, and the signal was slightly diluted after accounting for observed between-study heterogeneity in the RE2 model ('All' , p = 1.07 × 10 −5 ; 'Grade_B' , p = 7.99 × 10 −6 ).…”
Section: Discussionmentioning
confidence: 85%
“…Our results are in agreement with previous studies that demonstrated an association between 1p36.33 and endometriosis [34][35][36]. This locus contains markers located in or near the WNT4 gene, which plays an important role on the development of the female reproductive tract and steroidogenesis [37,38].…”
Section: Discussionsupporting
confidence: 93%
“…Gene symbols, expanded name and chromosome location are listed in Table 1 in alphabetical order for each of the 370 obesity genes. Similarly, 153 genes were found to be associated with human infertility and reproduction (Table 2) when searching the medical literature and based on genome-wide association, linkage and gene mutation or variant studies and 21 of these genes had a recognized role in obesity [32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Resultsmentioning
confidence: 99%